Estimation of the ecosystem carbon budget in South Korea between 1999 and 2008. Issue 6 (26th September 2013) - Yoo, Seongjin; Kwak, Doo‐Ahn; Cui, Guishan; Lee, Woo‐Kyun; Kwak, Hanbin; Ito, Akihiko; Son, Yowhan; Jeon, Seongwoo
Abstract: A carbon flux model, the vegetation integrated simulator for trace gases, was employed to estimate the carbon budgets of vegetation ecosystems in South Korea. The geographic information system was used to prepare the input variables for the model, such as climate, soil, and land‐cover data, from reliable national inventories. Model simulation results indicated that the annual average gross primary production, net primary production, and soil respiration (SR) for 10 years were 91.89, 40.16, and 62.91 Tg C year −1, respectively. The model also estimated a net ecosystem production with a value of 3.51 Tg C year −1 between 1999 and 2008. Such results indicate that the vegetation ecosystems of South Korea offset 3.3 % of anthropogenic emissions as a net carbon sink. Latitudinal and topographical gradients over the total simulation area were found for all estimates. In addition, the estimates varied between seasons and years, especially in estimates for biomass growth and carbon uptake, because of variations in the weather conditions. Finally, model validation was conducted using measured soil efflux and flux measurement data from the Gwangneung experimental forest (GEF). The estimated SR accounted for 81.6 % of the observed SR at the GEF site ( P < 0.005). Further, the model accounted well for the observed phase and amplitude of changes in the summer and autumn seasons.